Medicine prescribing pattern of dermatology outpatient department in tertiary level hospital at Dhaka City - Sarker, SK; Ali, CM; Khan, MI; Khan, MI; Rahman, H; Rahman, KA (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13241 J. Dhaka Med. Coll. 2012; 21(1): 66-68